A Comprehensive Analysis Identified the Key Differentially Expressed Circular Ribonucleic Acids and Methylation-Related Function in Pheochromocytomas and Paragangliomas - Yu, Anze; Li, Minghao; Xing, Changsheng; Chen, Danlei; Wang, Cikui; Xiao, Qiao; Zhang, Liang; Pang, Yingxian; Wang, Yong; Zu, Xiongbing; Liu, Longfei (Frontiers in Genetics, 2020)
Aims: To investigate the differentially expressed circular RNAs (circRNAs) and their potential functions in pheochromocytomas and paragangliomas (PCC/PGLs). Materials & Methods: We analyzed the expression levels of circRNAs through RNA sequencing in tumor and adjacent normal tissues from 7 PCC/PGL patients. Real-time qPCR was conducted to verify the key candidates identified in the sequencing data. GO and KEGG Pathway analyses were performed to predict the functions of these circRNAs. The circRNA-miRNA-mRNA coding-noncoding gene co-expression (CNC) networks were mapped to show the potential binding relationship between circRNAs and their targets in PCC/PGLs. Results: A total of 367 circRNAs were shown to have differential expression between tumor and normal samples. The top 3 histone-methylation-related circRNAs (hsa_circ_0000567, hsa_circ_0002897, hsa_circ_0004473) and their target miRNAs were identified and validated. The top 5 mRNAs, 88 miRNAs, and 132 circRNAs related to the pathogenesis were utilized to map the CNC network, and we observed that the interactions of these candidates with their target miRNAs regulated the procedure of histone-methylation, and further controlled the pathogenesis of PCC/PGLs. Conclusions: Our study is the first to provide the whole profile of differentially expressed circRNAs in PCC/PGLs, and our data indicate that the altered circRNAs may control the pathogenesis of PCC/PGLs by regulating the histone-methylation processes and act as potential biomarkers.